Exploring factors influencing digital literacy among higher vocational students based on quantitative evidence - Shun Xu; Ling Wang; Sha Zhu; Yangwei Dai (Scientific Reports)
Abstract In the era of digital economy, enhancing the digital literacy (DL) of higher vocational students (HVSs) is crucial for cultivating skilled talents in digital industries and promoting the high-quality development of vocational education. Previous research on DL mainly focused on higher education, teacher education, the field of library and information etc., but rarely investigated HVSs in detail, and constitutes a research gap that requires the attention of the vocational education community. To explore the current DL level of HVSs and to establish potential factors that will lead to its improvement, this study conducted a survey-based quantitative approach with 348 participants from a vocational college in H province. Pearson correlation analysis and regression analysis were used to systematically investigate the level of DL among HVSs and its influencing factors. Results show that the overall DL of HVSs is moderately high and the five factors of computer self-efficacy (CSE), Internet attitudes, social media competence (SMC), school organizational support, and teachers’ DL conveyance all had a positive predictive effect on HVSs’ DL. Among these factors, teachers’ DL education was found to be the strongest predictor. These results emphasize the importance of DL education for HVSs and provide a practical direction for improving HVSs’ DL.